2016
DOI: 10.5603/fm.a2015.0089
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of coronary sinus ostium

Abstract: CSO (22.09%). In 3 specimens the valve completely occluded the ostium. (Folia Morphol 2016; 75, 2: 264-267)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…At the Institute of Anatomy, Faculty of Medicine in Skopje, a few studies of primary cardiac malformations in congenital heart diseases associated with anomalies of embryonic aortic arches and coronary circulation were done. The results of these previous examinations (Korneti, Kargovska) made on heart specimens fixed in 10% formaldehyde, showed that congenital heart diseases most often (70.9%) were accompanied with anomalies of the aortic arch (interrupted, hypoplastic, vascular ring with right aortic arch and coarctation) [24] . The analysis of the branching pattern of the aortic arch showed that the most common variation was reduction of the number of branches to two (3.6%) with a. carotis communis sinistra arising from truncus brachiocephalicus (Zhivadinovik, 2000) [24,18] .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At the Institute of Anatomy, Faculty of Medicine in Skopje, a few studies of primary cardiac malformations in congenital heart diseases associated with anomalies of embryonic aortic arches and coronary circulation were done. The results of these previous examinations (Korneti, Kargovska) made on heart specimens fixed in 10% formaldehyde, showed that congenital heart diseases most often (70.9%) were accompanied with anomalies of the aortic arch (interrupted, hypoplastic, vascular ring with right aortic arch and coarctation) [24] . The analysis of the branching pattern of the aortic arch showed that the most common variation was reduction of the number of branches to two (3.6%) with a. carotis communis sinistra arising from truncus brachiocephalicus (Zhivadinovik, 2000) [24,18] .…”
Section: Discussionmentioning
confidence: 94%
“…The results of these previous examinations (Korneti, Kargovska) made on heart specimens fixed in 10% formaldehyde, showed that congenital heart diseases most often (70.9%) were accompanied with anomalies of the aortic arch (interrupted, hypoplastic, vascular ring with right aortic arch and coarctation) [24] . The analysis of the branching pattern of the aortic arch showed that the most common variation was reduction of the number of branches to two (3.6%) with a. carotis communis sinistra arising from truncus brachiocephalicus (Zhivadinovik, 2000) [24,18] . The second most common variation was increasing the number of branches to four due to separated arising of a. vertebralis sinistra between a. carotis communis sinistra and a. subclavia sinistra (2.7%) (Kargovska, Korneti 1985) (Zhivadinovik, 2000) [24,18] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This type was the most frequent (20.8 %) among the 53 PLSVC cases classified by Uemura et al (2012). Zhivadinovik et al (2016) studied 100 cadavers and reported a coronary sinus ostium diameter of 8.1 ± 1.51 mm. This diameter in our case was 22.9 mm, which was significantly larger than usual.…”
Section: Discussionmentioning
confidence: 99%
“…The orifice has a fold of endocardial tissue called Thebesian valve. Thebesian vavle is a remnant of caudal portion of the right valve of embryonic sinoatrial orifice [2]. It is situated in the diaphragmatic part of coronary sulcus.…”
Section: Basic Anatomymentioning
confidence: 99%